2015
DOI: 10.1111/tme.12207
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 and C‐reactive protein load in pre‐storage and post‐storage white blood cell‐filtered red blood cell transfusions in premature infants

Abstract: Because leukocytes in PRBC transfusions can be associated with many undesirable effects, leukoreduction is the best choice to prevent those effects. However, this method is still controversial. We demonstrated that using pre-storage and post-storage leukoreduction methods in erythrocyte transfusions did not change CRP or IL-6 levels, which are indicators of acute-phase response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For example, researches have demonstrated that changes in mesenteric blood flow velocity, reoxygenation, and reperfusion after transfusion could incite intestinal oxidative stress injury [20][21][22] . Furthermore, multiple immune factors such as IL-1β, IL-6, IFN-γ, and ICAM-1 have been shown to increase in circulation following RBC transfusion 23,24 . www.nature.com/scientificreports/…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researches have demonstrated that changes in mesenteric blood flow velocity, reoxygenation, and reperfusion after transfusion could incite intestinal oxidative stress injury [20][21][22] . Furthermore, multiple immune factors such as IL-1β, IL-6, IFN-γ, and ICAM-1 have been shown to increase in circulation following RBC transfusion 23,24 . www.nature.com/scientificreports/…”
Section: Discussionmentioning
confidence: 99%
“…For example, researches have demonstrated that changes in mesenteric blood flow velocity, reoxygenation, and reperfusion after transfusion could incite intestinal oxidative stress injury 20 22 . Furthermore, multiple immune factors such as IL-1β, IL-6, IFN-γ, and ICAM-1 have been shown to increase in circulation following RBC transfusion 23 , 24 . Studies have described a murine model of NEC instigated by transfusions after anemia, illustrating typical NEC-like gut injuries in the anemia-transfusion group within 48 h post transfusion due to Toll-like receptor-4-mediated injury and intestinal epithelial barrier dysfunction 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 796 records were excluded from screening titles and abstracts because of the pertinence of the study for review. The remaining 26 reports were read in full to con rm their relevance for the review, and 17 were excluded for failing to meet the inclusion criteria 24,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] ; thus, nine studies [19][20][21]25,[43][44][45][46][47] were included in this review.…”
Section: Study Inclusion Criteriamentioning
confidence: 99%
“…Until now, studies on TANEC have focused mainly on the following aspects: (1) mesenteric blood flow velocity altered after transfusion, and more fluctuant oxygenation was observed in patients with NEC 6 ; (2) re‐oxygenation and reperfusion accompanied by transfusion after anemia, which may cause oxidative stress injury in the intestine 7 ; (3) multiple immune factors (such as IL‐1β, IL‐6, IFN‐γ, and ICAM‐1) increased in circulation after RBC transfusion 8,9 ; and (4) recently, a study revealed that macrophages infiltrated the intestinal mucosa and subsequent RBC transfusion activated these macrophages via a TLR4‐mediated inflammatory response to cause bowel injury 10 . However, these studies cannot be applied to strategies for TANEC prevention or treatment clinically.…”
Section: Introductionmentioning
confidence: 99%